The materials sourcebook for design professionals - Thompson, Rob (Thames & Hudson, 2017)
"The knowledge in this book is fundamental to help designers choose the most appropriate materials. Getting it right not only leads to better design, but also means the least energy is consumed and waste produced. Regardless of application, the richness of information provides designers with endless possibilities to explore the most positive material experiences"--
Literaturverzeichnis Seite 536
Keywords: Material; Design